2021
DOI: 10.1038/s41598-020-78528-3
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extract (GbE) attenuates obesity and anxious/depressive-like behaviours induced by ovariectomy

Abstract: While several pieces of evidence link obesity and mood disorders in menopause, the mechanisms involved are not yet fully understood. We have previously demonstrated that Ginkgo biloba extract (GbE) both attenuated diet-induced obesity of male rats and restored serotonin-induced hypophagia in ovariectomized female rats. The present study aimed at exploring whether GbE treatment ameliorates ovariectomy-related obesity and anxious/depressive-like behaviours. Wistar female rats were either ovariectomized (OVX) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Indeed, this hypothesis is aligned with previous studies from our group in which the GbE 14-day supplementation reduced food intake, body weight gain, and visceral adiposity in DIO rats [15,16,18]. We have also reported that GbE modulated hypothalamic and hippocampal anorexigenic mechanisms after a 14-day treatment protocol, supporting a hypothesis for a time-dependent hypophagic effect [17][18][19][20][21]. That the GbE effect is time-dependent was also suggested in studies evaluating the modulation of memory.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Indeed, this hypothesis is aligned with previous studies from our group in which the GbE 14-day supplementation reduced food intake, body weight gain, and visceral adiposity in DIO rats [15,16,18]. We have also reported that GbE modulated hypothalamic and hippocampal anorexigenic mechanisms after a 14-day treatment protocol, supporting a hypothesis for a time-dependent hypophagic effect [17][18][19][20][21]. That the GbE effect is time-dependent was also suggested in studies evaluating the modulation of memory.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that the beneficial effects of GbE on glucose and cholesterol metabolism, insulin signaling, visceral adiposity, and energy homeostasis previously observed in both the DIO [15,16] and ovariectomized rats [20] might be related to the early modulation of the POMC pathway (Figure 5). dependent hypophagic effect [17][18][19][20][21]. That the effect is time-dependent was also suggested in studies evaluating the modulation of memory.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations